Power Factor Correction with Current Controlled Buck Converter for BLDC Motor Drive - P. Sarala; S. F. Kodad; B. Sarvesh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
Brushless DC motor is a synchronous machine that makes use of electronic commutation instead of mechanical commutator. Brushless DC motors makes use of inverter encompassing static switches for its operation. A simple bridge converter when used for BLDC drive as front end converter makes input source power factor to get reduced which is unacceptable in the power system. To avoid the distortions in the source voltage and source currents, Buck converter which was used as power factor correction (PFC) converter in this paper to improve the power factor. Presence of power electronic converters deteriorates system power factor effecting overall system performance. This paper presents buck converter for power factor correction in brushless DC motor drive system. Buck converter is operated with current control strategy rather to conventional voltage follower control. Simulation model was obtained using MATLAB/SIMULINK software and the brushless DC motor performance characteristics were shown for conditions with different DC link voltages and step variation in DC link voltage. Total harmonic distortion in source current was also presented.